Polymer optical fiber Bragg Gratings in CYTOP Fibers for angle measurement with dynamic compensation - Leal-Junior, Arnaldo; Theodosiou, Antreas; Díaz, Camilo; Marques, Carlos; Pontes, Maria José; Kalli, Kyriacos; Frizera-Neto, Anselmo (My University, 2018)
This paper demonstrates the use of polymer optical fiber Bragg gratings (POFBGs) for angle measurements over a range of different oscillatory frequencies. The POFBGs are inscribed in low-loss, cyclic transparent amorphous fluoropolymers (CYTOP) and are imprinted using the direct-write, plane-by-plane femtosecond laser inscription method. As the polymer has a viscoelastic response and given that the Young’s modulus depends on the oscillatory frequency, a compensation technique for sensor frequency cross-sensitivity and hysteresis is proposed and verified. Results show that the proposed compensation technique is able to provide a root mean squared error (RMSE) reduction of 44%, and a RMSE as low as 2.20° was obtained when compared with a reference potentiometer. The hysteresis reduction provided by the proposed technique is 55%, with hysteresis <0.01. The results presented in this paper can pave the way for movement analysis with POFBG providing higher sensitivity and low hysteresis over a large range of motion frequencies.
Keywords: Polymer optical fiber; Fiber Bragg gratings; CYTOP; Curvature sensor; Hysteresis